2011
DOI: 10.1002/chem.201100084
|View full text |Cite
|
Sign up to set email alerts
|

Facile Method for Development of Ligand‐Patterned Substrates Induced by a Chemical Reaction

Abstract: Patterned substrates have been widely used in various applications, including arrays of biomolecules and cells, highthroughput assays, and direct target sensing.[1] In practice, those demands have been achieved by either of or a combination of two strategies: 1) direct incorporation of biomolecules or functional-group-containing molecules into desired patterns and 2) generation of functional-group-presenting patterns by way of chemical conversions on the surface. The former encompasses microcontact printing (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…A trimethyl lock quinone (TLQ) moiety was originally developed by modifying Cohen's model for oxidative phosphorylation . The TLQ moiety is particularly advantageous because of its facile intramolecular ring cyclization reaction (δ‐lactonization) that can release a reporter molecule upon reduction . In this study, we focused on new TLQ reporter molecules to develop a fluorescent probe for NAD(P)H detection.…”
Section: Introductionmentioning
confidence: 99%
“…A trimethyl lock quinone (TLQ) moiety was originally developed by modifying Cohen's model for oxidative phosphorylation . The TLQ moiety is particularly advantageous because of its facile intramolecular ring cyclization reaction (δ‐lactonization) that can release a reporter molecule upon reduction . In this study, we focused on new TLQ reporter molecules to develop a fluorescent probe for NAD(P)H detection.…”
Section: Introductionmentioning
confidence: 99%
“…While such demand has been achieved on two dimensional surfaces by fluorescence, electrochemistry, XPS, etc, no efficient methods for use on three dimensional surfaces have been reported 7,8 . Recently, matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS), which directly provides information regarding surface compositions, has been actively used for surface analysis of self-assembled monolayers on gold [9][10][11][12][13] . In this report, we extended this strategy to three dimensional surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…www.chemeurj.org ology for investigating various cellular behaviors in response to changes in ligand density on the surface. [18,23] Since the discovery of RGD, substantial efforts have been made to identify additional ligands involved in cell adhesion. Yamada et al reported that Pro-His-Ser-Arg-Asn (PHSRN) found in the 9th type III domain of FN influences a 5 b 1 integrin-mediated cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported a patterning method on monolayers utilizing this quinone derivative. [18] On treatment of the surface with a reducing agent, the quinone is reduced to the corresponding hydroquinone and a cyclization reaction spontaneously takes a place to give amine functionality on the monolayer (Scheme 1 A). The resulting amino groups can be then tethered to a variety of (bio)molecules through amine-specific bioconjugation chemistry.…”
Section: Introductionmentioning
confidence: 99%